Evaluasi Sistem Pelacakan Resi Pada Website Shopee Express Menggunakan Pendekatan Pieces - Salamudin, Salamudin; Sutabri, Tata (LPPM UNIKA Santo Thomas Medan, 2025)
This study uses the PIECES framework, which has six important aspects: Performance, Information, Economy, Control, Efficiency, and Service, to assess the shipment tracking system on the Shopee Express website. Direct observation and system testing serve as the foundation for the study's qualitative descriptive methodology. The system's accuracy in displaying real-time tracking information and its performance on stable networks are demonstrated by the results. However, a number of drawbacks are discovered, including restricted service responsiveness on sluggish connections, no progress feedback during data loading, and no input validation. The system lacks user assistance features like history tracking and interactive guidance, despite being cost-effective and available without a login. The PIECES framework is a useful tool for determining web-based logistic tracking systems' advantages and shortcomings.